Digitalization Distribution of zakat through scholarships in improving the quality of education - Kamaruddin Syam; Arismunandar Arismunandar; Nurhikmah H (Himpunan Pengembang Kurikulum Indonesia, 2025)
Education scholarship services need to be digitized to facilitate access to information, support the transparency of zakat distribution, and improve the quality of education in Indonesia. Therefore, this research aims to develop a website for Badan Amil Zakat Nasional (BAZNAS) that supports improving the quality of education. This research uses the ADDIE approach, which consists of five stages: analysis, design, development, implementation, and evaluation. The needs analysis results are based on interviews with the head of BAZNAS and observation of the activities of students receiving education scholarships. This shows that the digitization of education scholarship information is essential. The design uses flowcharts, storyboards, and prototypes to make the developed website easy to use. Development by assessing validators of material and media experts, who show valid and very valid categories. The level of media practicality of the small group test shows that the developed website is efficient. The evaluation of the website that has been created shows the feasibility of the product to be used to support the achievement of the educational scholarship program. It can be concluded that the website that has been developed has proven to be effective in improving the quality of education in Indonesia. Abstrak Layanan beasiswa pendidikan perlu dilakukan digitalisasi untuk memudahkan akses informasi sehingga mendukung transparansi penyaluran zakat dan meningkatnya kualitas pendidikan di Indonesia. Maka dari itu, penelitian ini bertujuan untuk mengembangkan website Badan Amil Zakat Nasional (BAZNAS) yang mendukung peningkatan kualitas pendidikan. Penelitian ini menggunakan pendekatan ADDIE yang terdiri dari lima tahap yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Hasil analisis kebutuhan didasarkan pada wawancara dengan ketua BAZNAS dan observasi aktivitas para mahasiswa penerima beasiswa pendidikan menunjukkan bahwa digitalisasi informasi beasiswa pendidikan sangat diperlukan. Desain menggunakan flowchart, storyboard, dan prototype supaya website yang dikembangkan mudah digunakan. Pengembangan dengan melihat penilaian validator ahli materi dan media yang menunjukkan kategori valid dan sangat valid. Tingkat kepraktisan media dari uji kelompok kecil menunjukkan website yang dikembangkan sangat praktis. Evaluasi website yang telah dikembangkan menunjukkan kelayakan produk untuk digunakan untuk mendukung ketercapaian program beasiswa pendidikan. Dapat disimpulkan bahwa website yang telah dikembangkan terbukti efektif dalam meningkatkan kualitas pendidikan di Indonesia. Kata Kunci: beasiswa pendidikan; kualitas pendidikan; penyaluran zakat